2019
DOI: 10.1371/journal.pone.0215276
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry and spatial distribution of muscle glucose uptake in the lower limbs during walking measured using FDG-PET

Abstract: Purpose This study aimed to elucidate whether muscle activity (in terms of glucose uptake) between the legs can be considered symmetrical during walking. Furthermore, we aimed to determine whether the [ 18 F]-fluorodeoxyglucose was distributed heterogeneously throughout each muscle, and if so, whether areas of high uptake would be clustered. Methods Ten healthy participants walked on a treadmill at self-selected comfortable walking speed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…It was found that contraction in GM is highly non-uniform across its subdivisions during different motions. This is generally in agreement with previous EMG and FDG-PET studies [8,[11][12][13][14]. There was also a marked difference in the biomechanics of GM between the models with and without the consideration of non-uniform contraction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was found that contraction in GM is highly non-uniform across its subdivisions during different motions. This is generally in agreement with previous EMG and FDG-PET studies [8,[11][12][13][14]. There was also a marked difference in the biomechanics of GM between the models with and without the consideration of non-uniform contraction.…”
Section: Discussionsupporting
confidence: 91%
“…There are a number of studies on non-uniform muscle contraction, mostly using electromyography (EMG) [8,[11][12][13] or FDG-PET (monitor fluorodeoxyglucose (FDG) uptake through positron emission tomography (PET)) [14]. However, the reliability of using EMG as an approach to measure biomechanics of muscles is questionable due to uncertainties in the acquisition and conversion of EMG signals into biomechanical response of muscles.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]FDG PET can clearly identify the entire muscleactivated region (Figure 1). Utilizing PET advantages, several studies have successfully identified activated muscle areas during various exercises such as pinching, skiing, and pedaling [28][29][30][31][32]41].…”
Section: Radiopharmaceuticals For Pet Imaging Of Skeletal Musclementioning
confidence: 99%
“…Two-dimensional (2D) muscular activity distributions have been reported using surface electrodes allocated in an array 12 14 ; however, to the best of our knowledge, there are no reports of 3D activity distributions that include deep muscle. Although the 3D distribution of glucose metabolism in muscles could be evaluated by fluorodeoxyglucose-positron emission tomography (FDG-PET) 15 , whole-body radiation exposure is a concern.…”
Section: Introductionmentioning
confidence: 99%
“…Despite limited information regarding its mechanism, T2 was reported to demonstrate a high correlation with glucose uptake within the muscle in both whole muscle and per-pixel analyses 22 , and by analyzing T2 shifts before and after exercise per voxel units, analysis of local activity distributions within muscles has been reported 23 . However, as there are significant individual differences in muscle form and their internal structures 24 , and the 3-dimensional activation patterns of skeletal muscle differ significantly between subjects even when performing the same motor task 15 , there was no method of analyzing trends in local activity distribution common to multiple subjects. On the contrary, in the analysis of brain MRI, morphological standardization called “spatial normalization” has been performed by nonlinear registration of brain images in many subjects with a template image of a standard brain form, and then the common regions of signal intensity change within the subject group have been detected by statistical parametric mapping (SPM) 25 27 .…”
Section: Introductionmentioning
confidence: 99%